Kawasaki Disease in Children Older Than 10 Years: A Clinical Experience From Northwest India - Jindal, Ankur Kumar; Pilania, Rakesh Kumar; Guleria, Sandesh; Vignesh, Pandiarajan; Suri, Deepti; Gupta, Anju; Singhal, Manphool; Rawat, Amit; Singh, Surjit (Frontiers in Pediatrics, 2020)
Background: Kawasaki disease (KD) is predominantly seen in young children (<5 years). Diagnosis of KD is often delayed in older children and adolescents leading to a higher risk of coronary artery abnormalities (CAA). There is paucity of literature on KD in older children. Methods: Data were collated from a review of records of patients diagnosed with KD who were aged >10 years at time of diagnosis during the period January 1994-June 2019. Results: Eight hundred and sixty five patients were diagnosed to have KD during this period. Of these, 46 (5.3%; 26 boys and 20 girls) were aged 10 years or more at time of diagnosis. Median age at diagnosis was 11 years (range of 10-30 years). Median interval between onset of fever and diagnosis of KD was 12 days (range of 4-30). Eight patients (17.4%) presented with hypotensive shock. Coronary artery abnormalities (CAAs) were seen in 6 (13.04%) patients and 3 patients had myocarditis. Patients with CAAs were found to have significantly higher median platelet count and higher median C-reactive protein levels. First-line treatment included intravenous immunoglobulin. Adjunctive therapy was given in 5 patients (infliximab in 4 and steroids in 1). Median time between onset of fever and administration of IVIg was 13.5 days (range of 6-32). Total duration of follow-up is 2014.5 patient-months. Conclusion: Diagnosis of KD in children above 10 years is usually delayed and these patients are at higher risk of CAAs.